KONTRIBUSI KECERDASAN NATURALIS ANAK MENURUT FILOSOFI JEAN-JACQUES ROUSSEAU: STUDI LITERATUR - Ema Papuana Tekerop; Istiniah Istiniah; Rina Elisabeth; alfonso munte (Pedir Research Institut, 2021)
This paper is motivated by Jean-Jacques Rousseau's philosophy of naturalist intelligence with the presence of amour-propre or amour de soi-même and compassion. Then, through this attitude (self-love) the author sees this attitude as a contribution to children who have natural intelligence. The purpose of the study was to analyze Jean-Jacques Rousseau with various previous studies on naturalist intelligence in children itself. The research method uses literature review: the philosophy of Jean-Jacques Rousseau through his successors and previous research on naturalist intelligence. The results of the study both show and confirm the philosophy of Jean-Jacques Rousseau regarding amour-propre or amour de soi-même in children through the results of previous studies using various methods, research subjects and data used by previous researchers.